Therapeutic Antibody Against Phosphorylcholine Preserves Coronary Function and Attenuates Vascular 18F-FDG Uptake in Atherosclerotic Mice - Mia Ståhle; Johanna M.U. Silvola; Sanna Hellberg; Margreet de Vries; Paul H. A. Quax; Jeffrey Kroon; Petteri Rinne; Alwin de Jong; Heidi Liljenbäck; Nina Savisto; Anna Wickman; Erik S.G. Stroes; et al. (Elsevier Inc, 2022)
This study showed that treatment with a therapeutic monoclonal immunoglobulin-G1 antibody against phosphorylcholine on oxidized phospholipids preserves coronary flow reserve and attenuates atherosclerotic inflammation as determined by the uptake of 18F-fluorodeoxyglucose in atherosclerotic mice. The noninvasive imaging techniques represent translational tools to assess the efficacy of phosphorylcholine-targeted therapy on coronary artery function and atherosclerosis in clinical studies.